2016
DOI: 10.3389/fphar.2016.00480
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Pleurotus tuber-regium on Carbon- Tetrachloride Induced Testicular Injury in Sprague Dawley Rats

Abstract: The high rate of male infertility and the meager resources to manage same in sub Saharan Africa have necessitated the search for cost effective and available alternatives. Mushrooms have been used traditionally in folk medicine and as nutraceuticals. This study has investigated the effect of the wild mushroom Pleurotus tuber-regium on carbon tetrachloride (CCl4) deleterious effects on the reproductive system of male rats. Thirty six rats were divided into six groups of six animals each. Group I (negative contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The oxidative stress of the testicular germinal layer is a central cause of the intrinsic apoptotic cascade, which can trigger mitochondrial ROS generation and provoke hypogonadism (Aitken et al, 2014). In addition, CCl 4 reduced the secretion of testosterone, FSH and LH in rats through direct effects on the central nervous system and Leydig cells and/or indirectly by affecting the hypothalamic-pituitary estrogen receptor axis (Okolo, Siminialayi & Orisakwe, 2016; Noureen et al, 2017). CCl 4 enhanced cellular degeneration by increasing the production of H 2 O 2 and nitrite, which resulted in infertility/testicular dysfunction (Sahreen, Khan & Khan, 2013; Ojo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The oxidative stress of the testicular germinal layer is a central cause of the intrinsic apoptotic cascade, which can trigger mitochondrial ROS generation and provoke hypogonadism (Aitken et al, 2014). In addition, CCl 4 reduced the secretion of testosterone, FSH and LH in rats through direct effects on the central nervous system and Leydig cells and/or indirectly by affecting the hypothalamic-pituitary estrogen receptor axis (Okolo, Siminialayi & Orisakwe, 2016; Noureen et al, 2017). CCl 4 enhanced cellular degeneration by increasing the production of H 2 O 2 and nitrite, which resulted in infertility/testicular dysfunction (Sahreen, Khan & Khan, 2013; Ojo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The clear serum supernatant was then carefully aspirated and stored in a clean sample bottle for the determination of some biochemical parameters. Rats were sacrificed under ether anesthesia ( Okolo et al, 2016 ) and concussion stunning involving manually applied trauma on the head ( AVMA, 2013 ); the kidney and liver were excised, weighed, rinsed in saline, and preserved in 10% formalin for histopathological study.…”
Section: Methodsmentioning
confidence: 99%
“…Xu et al demonstrated the cancer effect of polysaccharide-protein complexes derived from PP [105]. On the other hand, other studies demonstrated that b-glucans derived from PTR could induce apoptosis against cancer cells and enhance the immunomodulatory and anti-tumor activities [106]. The high-level intake of Pleurotus mushroom intake can decrease the risk of cancer and other diseases.…”
Section: Dietary Fibermentioning
confidence: 99%